Chemical composition and antibacterial activity of essential oil Peperomia acuminata from Venezuelan Andes - Mora-Vivas, Flor D. (2016)
The genus Peperomia (Piperaceae) is well known for its ornamental species and ethnomedicinal uses. This paper aims to chemically characterize the essential oil of Peperomia acuminata Ruiz & Pav. from Mérida State, Venezuela, and determine its microbiological activity. The essential oil is obtained by hydrodistillation of the leaves and the separation of the components was performed by gas chromatography-mass spectrometry (GC/MS). Eight compounds (96.7%) were elucidated in the oil. The 2E dodecenal was found to be the major component (65%) followed by dodecanal (14.8%) and tetradecanal (9.2%). The essential oil showed high specificity against Gram positive bacteria Staphylococcus aureus ATCC (25923) and Enterococcus faecalis (29212) with a Minimum Inhibitory Concentration of 1 µL/mL. This is the first report about chemical composition of the essential oil from this specie therefore an important contribution to the study of the genus Peperomia.